Increasing Public Welfare Through Increasing Human Resources of Original Songket Weaving Craftsmanships in Nganjuk District - Ambarwati; Supheni, Indrian; Arintowati, Dyan; Wulandari, Vina; Ningrum, Dwi Septia (Universitas Negeri Semarang, 2024)
The background of this activity is the gap between active craftsmen and new craftsmen. This is a concern for weaving actors/craftsmen in Barong hamlet, Kedungrejo village, Tanjunganom District, Nganjuk regency. If no action is taken, the weaving culture will become extinct. On the one hand, weaving is a cultural heritage that must be maintained and preserved, but on the other hand, weaving is a promising source of income. Carrying out training activities to improve human resources for these weaving craftsmen means that two goals can be achieved at once, namely preserving ancestral culture and improving the welfare of weaving craftsmen which will have an impact on the community in general. The method chosen in implementing this activity was to provide basic weaving training for beginners, which continued with training so that it was hoped that they could become proficient. This activity was carried out in Barong hamlet, Kedungrejo village, Tanjunganom District, Nganjuk regency. The result of implementing this activity was the growth of new craftsmen who started from beginners/laymen about weaving and are now able to increase family income through weaving crafts.